An Analytical Solution for Sales of Seafood in District Karang Agung Ilir - Marlindawati, .; Misinem, .; Rizqi Dwi, Ramadhan (INTI International University, 2024)
The advent of internet technology has profoundly transformed information dissemination and commerce by providing continuous, global access. For Small and Medium Enterprises (UMKM) such as the Seafood District of Karang Agung Ilir—specializing in seafood products like shrimp, crabs, and squid—reliance on traditional market-based sales methods limits customer reach and hampers growth potential. This paper investigates the development of an innovative online-based sales information system aimed at modernizing and significantly improving the operational efficiency of the Seafood District. To evaluate the effectiveness of the proposed system, a System Usability Scale (SUS) test was conducted with 50 participants. The results yielded an average SUS score of 72, indicating that the system offers good usability but also highlights areas requiring further enhancement. The online platform is designed to provide 24/7 accessibility, optimize the sales process, and broaden the customer base beyond the local market. The anticipated advantages of this digital transition include reduced operational costs, enhanced customer service, and increased sales volume. By adopting online technology, the Seafood District of Karang Agung Ilir stands to strengthen its market presence and boost its competitiveness on a global scale.